Key acclimation responses to phosphorus deficiency in maize plants are influenced by exogenous nitric oxide - Ramos Artuso, Facundo Antonio (2018)
Improving phosphorus (P) acquisition and utilization in crops is of great importance in order to achieve a good plant nutritional state and maximize biomass production while minimizing the addition of fertilizers, and the concomitant risk of eutrophication. This study explores to which extent key processes involved in P-acquisition, and other acclimation mechanisms to low P supply in maize (Zea mays L.) plants, are affected by the addition of a nitric oxide (NO) donor (S-nitrosoglutathione, GSNO). Plants grown in a complete culture solution were exposed to four treatments performed by the combination of two P levels (0 and 0.5 mM), and two GSNO levels (0 and 0.1 mM), and responses to P-deprivation were then studied. Major plant responses related to P-deprivation were affected by the presence of the NO donor. In roots, the activity of acid phosphatases was significantly increased in P-depleted plants simultaneously exposed to GSNO. Acidification of the culture solution also increased in plants that had been grown in the presence of the NO donor. Furthermore, the potential capability displayed by roots of P-deprived plants for P-uptake, was higher in the plants that had been treated with GSNO. These results indicate that exogenous NO addition affects fundamental acclimation responses of maize plants to P scarcity, particularly and positively those that help plants to sustain P-acquisition under low P availability.